2014
DOI: 10.1016/j.rmed.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Airflow reversibility and long-term outcomes in patients with COPD without comorbidities

Abstract: In a large population of well characterized COPD patients without significant comorbidities, those demonstrating higher levels of reversibility at baseline presented better long-term outcomes even after controlling for other known prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
3
12
3
Order By: Relevance
“…This figure fell within the range of reversibility detected by other authors in a similar percentage of patients (21%–27.6%). 13 , 22 Furthermore, the FEV 1 of patients with a positive bronchodilator response in our study was higher than that of the other phenotypes. Similar results were reported by Calle Rubio et al, 18 although this finding was not reported elsewhere.…”
Section: Discussioncontrasting
confidence: 54%
“…This figure fell within the range of reversibility detected by other authors in a similar percentage of patients (21%–27.6%). 13 , 22 Furthermore, the FEV 1 of patients with a positive bronchodilator response in our study was higher than that of the other phenotypes. Similar results were reported by Calle Rubio et al, 18 although this finding was not reported elsewhere.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, Marin et al reported a result similar to ours in that a positive BDR was significantly associated with a prolonged time to first hospitalization. However, theirs was a retrospective study [21]. Our results were somewhat different from PLATINO study, in which a positive BDR according to the ATS criteria and wheezing in the last 12 months showed a higher risk of hospitalization [11].…”
Section: Discussioncontrasting
confidence: 78%
“…The usefulness of BDR positivity as a prognostic factor has been controversial [8, 11, 21]. BDR positivity favors a good treatment outcome in some studies, but demonstrates poor disease related outcomes in others.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that greater reversibility of airflow limitation at baseline was associated with better long-term outcomes in COPD patients without significant comorbidities. 39 Chronic inflammation in bronchiectasis leads to bronchomalacia or excessive collapsibility, resulting in obstructive airway physiology. 40 , 41 However, few studies have investigated the association between bronchiectasis and BDR in moderate-to-severe COPD patients.…”
Section: Discussionmentioning
confidence: 99%